The poor of Bogota : who they are, what they do, and where they live - Mohan, Rakesh; Hartline, Nancy (Washington, D.C., U.S.A. : World Bank, 1984)
This paper seeks to identify the correlates of poverty by examining in detail the composition and characteristics of the poor in Bogota. This done by analyzing two household surveys for Bogota in detail.
Includes bibliographical references: p. 82-85.
oif 15/04/2019
Loans
Keywords: Poor; Poverty; Colombia--Bogotá